Distinguishing the role of positivity bias, cognitive impairment and emotional reactivity in the deontological preference in multiple sclerosis during moral dilemmas: a social cognition study protocol - Zikos, Laurent; Degraeve, Béatrice; Pinti, Antonio; Poupart, Julien; Norberciak, Laurène; Kwiatkowski, Arnaud; Donze, Cécile; Lenne, Bruno (Frontiers in Psychology, 2024)
Background: Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the central nervous system characterized by a broad and unpredictable range of symptoms, including cognitive and sociocognitive dysfunction. Among these social-cognitive functions, moral judgment has been explored in persons with MS (PwMS) using moral dilemmas, where participants must decide whether to sacrifice one person to save a greater number. Opting for such a sacrifice reflects utilitarian reasoning (sacrificing one for the benefit of many is deemed acceptable), while refusing reflects deontological reasoning (such sacrifice is considered morally wrong). Compared to controls, PwMS have been shown to make greater deontological moral choices in such dilemmas.Objectives: While PwMS have demonstrated a higher tendency for deontological moral choices in moral dilemmas compared to controls, the underlying determinants of this reasoning pattern remain unclear. In this project, we aim to investigate cognitive, emotional, and motivational factors that may explain deontological decision-making in MS.We will recruit a sample of 45 PwMS and 45 controls aged 18-55 years. The type of response, deontological or utilitarian, to a series of 20 vignettes of moral dilemmas will constitute the primary outcomes. Global cognitive performance, positivity bias, alexithymia and empathy levels as well as emotional reactivity measured by electrodermal activity (EDA) during moral dilemmas will be secondary outcomes.Ethics and dissemination: Ethics approval was granted by a national ethical committee (CPP Ouest III, national number 2023-A00447-38). The project is sponsored by the ARSEP Foundation. Findings will be presented at national and international conferences, as well as published in peer-reviewed scientific journals.